2007
DOI: 10.1007/s10637-007-9089-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and pharmacokinetics of the novel anticancer drug, SYUIQ-5, in the rat

Abstract: SYUIQ-5, a novel telomerase inhibitor, has demonstrated antitumor activity in nude mouse studies. The objective of the present study was to examine the metabolism and pharmacokinetics of SYUIQ-5 in rats. The plasma pharmacokinetics of SYUIQ-5 was nonlinear following i.p. administration at 15, 30 and 60 mg/kg. SYUIQ-5 metabolism in rat liver microsomes followed Michaelis-Menten kinetics, with Km and Vmax values of 12.3 microM and 2.01 nmol/min/mg protein, respectively. Ketoconazole significantly inhibited the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Similar effects are also observed in leukemia cells [9]. These three quindoline derivatives have demonstrated substantial antitumor activity in nude mouse studies and the biotransformation and pharmacokinetics of SYUIQ-5 have been clearly described in our previously published paper [5]. SYUIQ-F5 was modified from SYUIQ-5.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Similar effects are also observed in leukemia cells [9]. These three quindoline derivatives have demonstrated substantial antitumor activity in nude mouse studies and the biotransformation and pharmacokinetics of SYUIQ-5 have been clearly described in our previously published paper [5]. SYUIQ-F5 was modified from SYUIQ-5.…”
supporting
confidence: 54%
“…1) is a novel quindoline derivative synthesized by the School of Pharmaceutical Sciences, Sun Yat-sen University. SYUIQ-F5 has been shown to interfere with telomere replication by blocking the elongation step catalyzed by both telomerasedependent and telomerase-independent mechanisms like its homologues such SYUIQ-5 and SYUIQ-FM05, which were also synthesized by Sun Yat-sen University [1][2][3][4][5]. Considerable evidence suggested that stabilization of G-quadruplex structures could directly inhibit telomerase activity and might cause down-regulation for the transcription of some oncogenes including G-quadruplex forming sequence in their promoters, such as bcl-2, c-myc, and c-kit [1,[6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyp3A is the primary enzyme involved in SYUIQ-5 metabolism in rat liver microsomes. SYUIQ-5 induces the mRNA and protein of rat Cyp1A1 and 1A2 in a dose-dependent manner, while SYUIQ-5 does not affect the expression and activity of Cyp2B1/2 and 2E1 [42]. SYUIQ-5 has also demonstrated substantial antitumor activity in nude mouse studies (unpublished data, Huang et al).…”
Section: Syuiq-fm05 Strongly Inhibits Blood Vessel Growth An Effect mentioning
confidence: 94%
“…Newer agents, including SYUIQ-5 [172] and AQ4N, are also metabolized by CYP1A1. Like many other chemotherapeutic agents, AQ4N is activated through metabolic processes.…”
Section: Cyp1a1 and Drug Metabolismmentioning
confidence: 99%